Identification of YAP regulators through high-throughput screening and NanoBiT-based validation-drug repositioning for cancer therapy - Ji-Youn Lim; Eui-Hwan Choi; Yujeong Kim; Minseong Kim; Dongkyu Choi; Wantae Kim; Boksik Cha (Animal Cells and Systems)
Yes-associated protein (YAP), a key co-transcription factor of the Hippo pathway, is a promising drug target for cancer therapy due to its critical role in promoting cell proliferation, survival, and tumor progression when dysregulated. While most Hippo pathway-targeting drugs focus on disrupting TEAD-YAP interactions or modulating the MST or LATS kinase cascade, new approaches are needed to identify small molecules that regulate YAP activity. In this study, we conducted high-throughput screening of FDA-approved drugs to discover potential YAP modulators. Using a NanoBiT-based system, which enables real-time and quantitative measurement of protein interactions, combined with phenotype-based assays in EGFP-YAP-expressing cells, we identified compounds that activate or inhibit YAP function. Among the identified YAP regulators, the microtubule destabilizer vinorelbine promoted YAP nuclear localization and transcriptional activation, while the antipsychotic drug thioridazine enhanced YAP phosphorylation at Ser127, resulting in its cytoplasmic retention and reduced transcriptional activity, effectively suppressing cancer cell growth. These findings demonstrate the potential of FDA-approved drugs in modulating YAP activity and present a novel screening strategy for developing YAP-targeting therapeutics. Furthermore, this approach can be extended to identify modulators of other signaling pathways, advancing drug discovery for a wide range of diseases.